A kind of LQ non-zero sum differential game of backward stochastic differential equation with asymmetric information. (November 2018) - Wang, Guangchen; Xiao, Hua; Xiong, Jie
Abstract: This paper focuses on a kind of LQ non-zero sum differential game driven by backward stochastic differential equation with asymmetric information, which is a natural continuation of Wang and Yu (2010), Wang and Yu (2012). Different from Wang and Yu (2010) and Wang and Yu (2012), a realistic motivation for studying this kind of game is provided, and some feedback Nash equilibrium points are uniquely obtained by forward–backward stochastic differential equations, their filters and the corresponding Riccati equations with Markovian setting.